Estudo de egressos do Sistema de Organização Modular de Ensino (SOME) na Amazônia: análise da política pública para o acesso ao ensino superior em Santarém/PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The Modular Education Organization System (SOME), implemented in 1980 in Pará, aims to guarantee access to secondary education in rural regions of the state. Although it was a public policy that presents several advantages for Education in the Amazon of Pará, it presents challenges to be faced for the continuity of studies and access to the world of work. Thus, we aim to analyze the impacts/challenges of SOME as a public policy for the possible insertion of its graduates into higher education in the Amazonian context. As specific objectives: i) carry out a Systematic Literature Review (RSL) on SOME and studies of graduates in CAPES databases; ii) present the historical path of SOME since its creation, focusing on the Santarém Center today; ii) locate graduates of SOME Polo Santarém, from 2019 to 2023, identifying them by region and helping to generate maps of their locations; and, iii) outline the profile of graduates from this center who were approved in selection processes for public and non-profit HEIs in the municipality of Santarém–PA. The study is qualitative in nature, with bibliographic and documentary research, whose structure follows the Scandinavian model, organized by texts in the form of articles and book chapters (published or unpublished), distributed in sections and subsections. As for the results, we highlighted: the appreciation of the historical context to understand the evolution of SOME in serving rural populations, alleviating the lack of access to secondary education; SOME Polo Santarém has played a fundamental role in guaranteeing the right to education and promoting basic training for adolescents, young people and adults in 64 rural communities, with 3.120 students enrolled in 2024; however, in the period from 2019 to 2023 we confirmed 2.766 graduates from this Center and only 118 of them were approved to pursue a degree in public and non-profit HEIs, in Santarém/PA. The challenges indicate possible difficulties due to the context studied, highlighting the urgency in reviewing not only the secondary education policy in Pará, but the policy for access to higher education in HEIs in the region, considering the reality of rural populations in the Amazonian context.
Keywords: Política pública educacional; Ensino médio; Sistema de Organização Modular de Ensino; SOME; Egressos - Estudo; CNPQ::CIÊNCIAS SOCIAIS APLICADAS